2013
DOI: 10.3146/ps12-15r3.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lactofen and 2,4-DB Combinations on Peanut Injury and Yield

Abstract: Lactofen plus crop oil adjuvants are increasingly being used to combat acetolactate synthaseresistant weeds in peanut production. To control a broader spectrum of weeds, it is desirable to mix 2,4-DB with lactofen. However, lactofen can be highly injurious to peanuts. It is unknown if the addition of 2,4-DB will exacerbate or prolong the injury observed by lactofen. Experiments were conducted in Citra and Jay, FL in 2011 and 2012 to examine the impact of lactofen, 2,4-DB and lactofen + 2,4-DB applied at 15, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Peanut has been shown to be extremely tolerant to applications of 2,4-DB (Baughman et al 2002;Faircloth and Prostko Ferrell et al 2013). Surprisingly, 10% less injury was observed 21 DAIT from 2,4-DB plus acifluorfen plus bentazon reapplied at a 15 d interval compared to acifluorfen plus bentazon alone reapplied at a 15 d interval.…”
Section: Sequential Applicationmentioning
confidence: 96%
See 2 more Smart Citations
“…Peanut has been shown to be extremely tolerant to applications of 2,4-DB (Baughman et al 2002;Faircloth and Prostko Ferrell et al 2013). Surprisingly, 10% less injury was observed 21 DAIT from 2,4-DB plus acifluorfen plus bentazon reapplied at a 15 d interval compared to acifluorfen plus bentazon alone reapplied at a 15 d interval.…”
Section: Sequential Applicationmentioning
confidence: 96%
“…Another study investigated application timing of saflufenacil on peanut and found that despite foliar injury after applications (up to 34%), saflufenacil could safely be applied up to 45 d after emergence and without reducing yield (>95% of nontreated) (Morichetti et al 2012). Similarly, lactofen applied 15, 30, and 45 d after planting resulted in 29%, 22%, and 28% foliar injury 7 d after treatment, respectively, but yields were not reduced (Ferrell et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When averaged over TOD, the lactofen program was more injurious than the imazapic program (Table 6). Peanut injury from lactofen has been observed in other research ranging from 20 to 48%, with no observed yield losses (Boyer et al, 2011;Ferrell et al, 2013). However, yield losses of 5% were observed from applications of lactofen applied approximately 60 d after planting (Dotray et al, 2012).…”
Section: Resultsmentioning
confidence: 71%
“…Paraquat reduced yield of the runner type peanut cultivar`York following application 21 days after cracking while application 7, 14, or 28 days after cracking did not reduce yield . Lactofen may also cause leaf necrosis and bronzing in peanut; however, this injury does not result in yield loss Ferrell et al 2013;Grichar and Dotray 2011;.…”
Section: Pyroxasulfone Tank-mixturesmentioning
confidence: 99%